Growth and Spectral Investigation of BiSCl Crystals - KUMARARAMAN, S.; SELVARAJU, K.; RAVICHANDRAN, T. (Asian Journal of Chemistry, 2010)
Bismuth sulphochloride (BiSCI) has been prepared by the reaction of BiCl3 dissolved in H2SO4 and acetic acid in silica gel. The IR and Raman spectra were recorded in the range of 600-50 cm-1. The IR spectra reveal that the frequency bands are sensitive to sulphur substitution and the Raman spectra show that the bands below 200 cm-1 are halogen sensitive.